Surgical, non-traumatic splenopathies - Ivonne López Masó; Rafael Trinchet Soler; Manuel García Artiles; Ada Arlenis Pérez Mayo (Medisur)
As our modern-day understanding about the role of the spleen in the immune system has developed, indications for splenectomies have also changed. Illnesses like idiopatic thrombocytopenic purple, hereditary spherocytosis, sickle cell anemia, beta thalassemia, portal hypertension and other non-traumatic disseases that carry out with congestive splenomegaly and hypersplenism, find an effective alternative with the total or partially splenectomy. We presented the Good Clinical Practices Guideline for Portal hypertension, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba, March, 2005).